Degradation of Antibiotics in Wastewater: New Advances in Cavitational Treatments - Emanuela Calcio Gaudino; Erica Canova; Pengyun Liu; Zhilin Wu; Giancarlo Cravotto (Molecules, 2021)
Over the past few decades, antibiotics have been considered emerging pollutants due to their persistence in aquatic ecosystems. Even at low concentrations, these pollutants contribute to the phenomenon of antibiotic resistance, while their degradation is still a longstanding challenge for wastewater treatment. In the present literature survey, we review the recent advances in synergistic techniques for antibiotic degradation in wastewater that combine either ultrasound (US) or hydrodynamic cavitation (HC) and oxidative, photo-catalytic, and enzymatic strategies. The degradation of sulfadiazine by HC/persulfate (PS)/H2O2/α-Fe2O3, US/PS/Fe0, and sono-photocatalysis with MgO@CNT nanocomposites processes; the degradation of tetracycline by US/H2O2/Fe3O4, US/O3/goethite, and HC/photocatalysis with TiO2 (P25) sono-photocatalysis with rGO/CdWO4 protocols; and the degradation of amoxicillin by US/Oxone®/Co2+ are discussed. In general, a higher efficiency of antibiotics removal and a faster structure degradation rate are reported under US or HC conditions as compared with the corresponding silent conditions. However, the removal of ciprofloxacin hydrochloride reached only 51% with US-assisted laccase-catalysis, though it was higher than those using US or enzymatic treatment alone. Moreover, a COD removal higher than 85% in several effluents of the pharmaceutical industry (500–7500 mg/L COD) was achieved by the US/O3/CuO process.